The law governing marriage, divorce and related issues in Sri Lanka - Nafees, Seeni Mohamed (2014)
Sri Lanka is a multi-ethnic, multi-religious and multi-cultural country where Buddhists, Hindus, Muslims, Christians, and Burghers inhabit.The major ethnicity of the country is Sinhalese who represents 74% of the population.Tamils and Muslims are main minorities of the country.At present, almost nine pieces of legislation govern matrimonial matters in Sri Lanka.Of which the general law and personal laws are significant. While marriages of Tamils are governed by the general law, Sinhalese may choose either general law or customary law.Muslim marriages are governed by Muslim personal law that is based on the Muslim Marriage and Divorce Act 1951.In this sense, different laws govern different ethnicity of the country and there is no uniformity in regulating family matters which render the issues more complicated.Therefore, this paper strives to investigate family law in Sri Lanka covering whole societies and proposes some suggestions based on need of the modern times.For this purpose, a qualitative research methodology is adopted.The study reveals that although a number of reforms have been introduced from time to time, there is still a need to adopt more practical approach in implementing the legislation on matrimonial matters.Especially, the Muslim Marriage and Divorce Act that was enacted in 1951 has not been revised for long time and it needs to be reformed in order to give effect to needs in line with social changes taking place globally.Although the law governing family issues of other ethnicities has gone through some important changes, there are a lot to be reformed.